Monitoring Heart Rate And Temperature Based On The Internet Of Things - Sumber; Rangga Adi Firmansyah; Bambang Guruh I (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2019)
Monitoring and measurement of body temperature is very important to know the condition of the patient. The body temperature has associated with a number of human heartbeat, little change in body temperature can significantly affect the performance of high cardiac health problems this causes the need for health monitoring. IOT helps to move from manual heart rate monitoring system for heart rate monitoring system remotely. The purpose of this study is to develop the monitoring heart rate and temperature based Internet of Things. This tool can see the dawn of the body and the value of BPM from a distance. The way the device is very simple to use cardiac leads in Lead II to obtain the value of BPM and DS18B20 temperature sensor to measure the body temperature will be displayed on Thingspeak through ESP32 module.